NÆRBILLEDER OG MODFORTÆLLINGER - INTERMEDIALITET, ERINDRING OG HISTORIEFREMSTILLING HOS KLUGE, SEBALD OG FOER - Tanderup, Sara (K&K - Kultur og Klasse, 2014)
CLOSE-UPS AND COUNTER STORIES | Recently, several literary works have appeared which use formal experiments and intermedial strategies to thematize memory and history. Authors such as Alexander Kluge, W.G. Sebald, Daniel Mendelsohn, Monica Maron, Jonathan Safran Foer, Don DeLillo and Aleksandar Hemon include other, primarily visual, media such as film, photographs and drawings, in their works while dealing with historical events like the Holocaust or the 9/11 terror attack. My article discusses this tendency, analyzing works by Kluge, Sebald and Foer. They all work with photographs in their texts. I trace the differences between them, following how ’foto-fiction’ as a genre has developed during the last three decades while arguing that Kluge, Sebald and Foer can all be read as part of the same tendency: Inspired by Andreas Huyssen’s idea of a modern memory culture, I suggest that the modern intermedial works can be read as an expression of a current cultural situation brought about by changes in the mediascape. Of course, books with pictures have always existed, however, the modern works are different from the typical illustrated novel as well as traditional history books, since they do not use the visual material to illustrate or document the story. Rather, images and text are brought together to introduce some tensions; to navigate between fiction and documentary, between an intimate remembering gaze and the ’objective’ writing of history. Intermediality thus becomes a tool to reflect upon modern conditions of writing history.